Hospital service for ischemic stroke patients in Brazilian countryside: are we still in the ‘80s? - Antonio Fernando Ribeiro Silva Junior; Gabriel Calasans dos Santos; Carla Martins Kaneto; Pedro Antonio Pereira de Jesus; Paulo Roberto Santana de Melo (Arquivos de Neuro-Psiquiatria)
Background Stroke is one of the most common causes of death and incapacity in the world. The benefits of reperfusion therapies and hospitalization in neurologic intensive care units (ICUs) are undeniable. However, these treatments are not widely available in a continental-sized country like Brazil.